2008
DOI: 10.1080/07399330802523618
|View full text |Cite
|
Sign up to set email alerts
|

Striving to Make a Difference: Health Care Worker Experiences With Intimate Partner Violence Clients in Tanzania

Abstract: In this article we describe health care workers' (HCWs') experiences and perceptions of meeting clients exposed to intimate partner violence (IPV). Qualitative content analysis of in-depth interviews from 16 informants resulted in four main themes. The first, "internalizing women's suffering and powerlessness," describes HCWs' perceptions of violence, relating it to gender relations. The second, "caught between encouraging disclosure and lack of support tools," refers to views on possibilities for transparency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 18 publications
1
29
0
4
Order By: Relevance
“…A qualitative study on health care worker perceptions about intimate partner violence, conducted in DSM, highlighted their frustrations at women’s reluctance to disclose abuse despite their being given evidence from the victims’ families or friends. The study concluded women consider abuse to be a shameful domestic matter or that revealing the violence would cause the woman stigma [39]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative study on health care worker perceptions about intimate partner violence, conducted in DSM, highlighted their frustrations at women’s reluctance to disclose abuse despite their being given evidence from the victims’ families or friends. The study concluded women consider abuse to be a shameful domestic matter or that revealing the violence would cause the woman stigma [39]. …”
Section: Discussionmentioning
confidence: 99%
“…hospital registration, and indirect costs, e.g. transport) that may prohibit women from seeking help [32,39]. A study from Uganda found that the out-of-pocket expenditure related to a single incident of partner violence amounted to $5.00 from a health centre and $10.00 when seeking police intervention – costs that are significant when considering the Gross National Income per capita of $340 [44].…”
Section: Discussionmentioning
confidence: 99%
“…On a systems level, HCW concerns include lack of time during consultations (1618), lack of training for HCWs, both prequalification and in-service (17, 19), weak referral networks (16, 17, 19), lack of confidence in management support (20), insufficient flexibility, and policy constraints (10). On a policy level, political commitment translated into clear policies and protocols is necessary for successful IPV intervention (20, 21).…”
mentioning
confidence: 99%
“…IPV was found to be a ‘hidden agenda’ because both HCWs and clients had difficulties to bring up the issue of violence. For the HCWs, this became a challenge even if they clearly indicated a desire to make a difference and identified the need for training and guidelines (28). …”
mentioning
confidence: 99%